2008
DOI: 10.1002/j.2325-8012.2008.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Exit Discrimination in Major League Baseball: 1990–2004

Abstract: Using a panel study of annual Major League Baseball (MLB) data (1990‐2004), we do not find evidence that race affects the career duration of black hitters. Our findings are inconsistent with results from a study by Jiobu (1988) who used 1971‐1985 data that found that race decreased career length, ceteris paribus, for black hitters but not Hispanics. The difference in results could be due to our use of seasonal‐variant data; Jiobu used only career statistics in his research. Another interpretation of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…First, both age and racial diversity have been studied in their connection to team performance in professional sports teams, including baseball teams (Timmerman, 2000). In particular, a number of studies have identified race as a particularly salient feature in sports teams (Cunningham, Choi, & Sagas, 2008; Groothuis & Hill, 2008; Kahn & Sherer, 1988; Stone, Lynch, Sjomeling, & Darley, 1999). Other sports studies have highlighted the importance of country of origin and identified it as a growing phenomenon—the unmistakable influx of international professional sports players in both the MLB and in the National Basketball Association (NBA; Eschker, Perez, & Siegler, 2004; Sakuda, 2012).…”
Section: Faultlines: a Brief Reviewmentioning
confidence: 99%
“…First, both age and racial diversity have been studied in their connection to team performance in professional sports teams, including baseball teams (Timmerman, 2000). In particular, a number of studies have identified race as a particularly salient feature in sports teams (Cunningham, Choi, & Sagas, 2008; Groothuis & Hill, 2008; Kahn & Sherer, 1988; Stone, Lynch, Sjomeling, & Darley, 1999). Other sports studies have highlighted the importance of country of origin and identified it as a growing phenomenon—the unmistakable influx of international professional sports players in both the MLB and in the National Basketball Association (NBA; Eschker, Perez, & Siegler, 2004; Sakuda, 2012).…”
Section: Faultlines: a Brief Reviewmentioning
confidence: 99%